Research and Implementation of New Energy Vehicle Servo Motor EMC Testing System. Issue 1 (March 2021) - Li, Peipei; Deng, Qingjun; Zhao, Yi; Hu, Jianyu; Liu, Yong; Zhao, Ying
Abstract: This paper studies the research status of electronic and electrical parts of new energy vehicles and analyzes the working principle of new energy vehicle servo motor electromagnetic compatibility (EMC) test device. Then developed a general EMC auxiliary test system for vehicle servo motor. The test result curve of the auxiliary test system is presented. The results show that the entire auxiliary system meets the requirements of standard test methods. And it can provide EMC testing services, technical consulting services and EMC comprehensive solutions for component manufacturers.